Classificação de marcas comerciais de arroz - (:unkn) unknown (Universidade Federal do Pampa, 2015)
The work evaluates periodically identity parameters required by the Brazilian law on white polished white rice brands of Rio Grande do Sul. Ten rice brands on benefited group, polished subgroup, long and thin grain class and type 1 were evaluated humidity for capacitance and classification according to the guide proposed by the Ministry of Agriculture, Livestock and Food Supply described in the Normative Instruction number 6, verifying the amount of broken, yellow, peck, musty, ragged, plastered and unhulled grains or containing foreign matter and impurities. The more incident defects were tested differences on brands and the Pearson product-moment correlation coefficient. The limit recommended by the law overcame the in the samples 5, 6 and 9, for broken, yellow and/or ragged grains. Initially, there were remarkable differences between broken, yellow, peck and ragged grains; in the following months the samples showed differences on the presence of broken and yellow grains. The prices were related negatively to the incidence of defects which had incidence linked to positive correlations.
Keywords: Arroz polido; Defeitos; Grãos quebrados; Grãos amarelos; Grãos rajados; Polished rice; Defects; Broken grains; Yellow grains; Brindle grains; CNPQ::CIENCIAS AGRARIAS